Optimal Contract Pricing of Distributed Generation Under a Competitive Framework - Lopez-Lezama, J. M.; Padilha-Feltrin, A. [UNESP]; Contreras, J.; Munoz, J. I.; IEEE (Ieee, 2010)
A bilevel programming approach for the optimal contract pricing of distributed generation (DG) in distribution networks is presented. The outer optimization problem corresponds to the owner of the DG who must decide the contract price that would maximize his profits. The inner optimization problem corresponds to the distribution company (DisCo), which procures the minimization of the payments incurred in attending the expected demand while satisfying network constraints. The meet the expected demand the DisCo can purchase energy either form the transmission network through the substations or form the DG units within its network. The inner optimization problem is substituted by its Karush-Kuhn-Tucker optimality conditions, turning the bilevel programming problem into an equivalent single-level nonlinear programming problem which is solved using commercially available software.
Keywords: Bilevel programming; distributed generation